High performance chelation ion chromatography - Nesterenko, Pavel (RSC chromatography monographs, 2010)
Established ion chromatography techniques have changed little since the 1980s but a new technique, high performance chelation ion chromatography (HPCIC), has revolutionized the area. HPCIC enables a much greater range of complex samples to be analyzed and this is the first comprehensive description of its use in the trace determination of metals. Written by world leaders in the field, it is aimed at professionals, postgraduates, chromatographers, analytical chemists, and industrial chemists. The book describes the underlying principles which give rise to the special selectivities that can be c.